Bilateral Primary Fallopian Tube Adenocarcinoma – A Rare Case - C Bhavani; P.V. Ramana Babu; E. Sudhakar Reddy; M. Neeraja (International Journal of Medical Research and Review, 2014)
Although fallopian tubes are a common site of metastases, primary fallopian tube carcinoma is considered a rare disease and is often mistaken histologically and clinically for ovarian cancer. The etiology is poorly understood and presenting symptoms are variable and non-specific, with preoperative diagnosis rarely entertained. We put forth our experience of a case of bilateral primary fallopian tube carcinoma which was histopathologically diagnosed after being misinterpreted on ultrasonography.